Using the SLEDGE package on Sturm-Liouville problems having nonempty essential spectra. - Eastham, Michael S. P.; Fulton, Charles T.; Pruess, Steven
We describe the performance of the Sturm-Liouville software package SLEDGE on a variety of problems having continuous spectra. The code's output is shown to be in good accord with a wide range of known theoretical results.
Keywords: Sturm-Liouville problems; Spectral density functions